Evaluation of centralization ability and canal transportation of root canals prepared with three commercially available pediatric rotary files - K Harshita Reddy; Sridhar Mukthineni; A J Sai Sankar; Y Samatha; K Pranitha; K Siva Sankar (Wolters Kluwer Medknow Publications, 2022)
Background: The complex root canal anatomy of primary root canals is considered to be most challenging. The quality of the root canal preparation plays a significant role in the success of endodontic treatment. Now, there are very few root canal instruments that are capable of cleaning the canal three dimensionally. To evaluate the efficacy of root canal instruments, various technologies have been used; one of the most reliable strategies was cone-beam computed tomography (CBCT). Aim: The aim of this study is to compare the centralization ability and canal transportation of three commercially available pediatric rotary file systems using CBCT analysis. Materials and Methods: Thirty-three extracted human primary teeth with a minimum 7 mm root length were randomly divided into three groups (group I - Kedo-SG Blue, group II - Kedo-S Square, and group III - Pro AF Baby Gold). Biomechanical preparation was done according to the manufacturers instructions. Pre- and postinstrumentation CBCT images were taken for each group to evaluate the remaining dentin thickness thereby assessing the centering ability and the canal transportation ability of different file systems. Results: Significant difference was noticed in canal transportation and centering ability between the three tested groups. Mesiodistal canal transportation was significant at all three levels, whereas buccolingual canal transportation was significant only at the apical third of the root. However, Kedo-SG Blue and Pro AF Baby Gold showed lesser canal transportation compared to Kedo-S Square rotary file system. Mesiodistal centering ability was significant at cervical and apical thirds of the root with Kedo-S Square rotary file system maintaining less canal centricity. Conclusions: All three file systems tested in the study were effective in removing the radicular dentin. However, Kedo-SG Blue and Pro AF Baby Gold rotary file systems showed comparatively less canal transportation and more centering ability than Kedo-S Square rotary file system.